Heterostructures and quantum devices - Einspruch, Norman G.; Frensley, William R. (VLSI electronics, 1994)
Heterostructure and quantum-mechanical devices promise significant improvement in the performance of electronic and optoelectronic integrated circuits (ICs). Though these devices are the subject of a vigorous research effort, the current literature is often either highly technical or narrowly focused. This book presents heterostructure and quantum devices to the nonspecialist, especially electrical engineers working with high-performance semiconductor devices. It focuses on a broad base of technical applications using semiconductor physics theory to develop the next generation of electrical engineering devices. The text covers existing technologies and future possibilities within a common framework of high-performance devices, which will have a more immediate impact on advanced semiconductor physics-particularly quantum effects-and will thus form the basis for longer-term technology development.